2014
DOI: 10.1038/srep05555
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dl-3n-butylphthalide on Learning and Memory Impairment Induced by Chronic Intermittent Hypoxia-Hypercapnia Exposure

Abstract: Cognitive impairment is a common finding in patients with chronic obstructive pulmonary disease (COPD), but little attention has been focused on therapeutic intervention for this complication. Chronic intermittent hypoxia hypercapnia (CIHH) exposure is considered to be responsible for the pathogenesis of COPD. Dl-3n-Butylphthalide (NBP), extracted from Apium graveolens Linn, has displayed a broad spectrum of neuroprotective properties. Our study aimed to investigate the potential of NBP on CIHH-induced cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…Previous studies have shown that Bcl2 exerts an antiapoptotic effect, 15 whereas Bax participates in the induction of apoptosis; 16 activation of C-caspase3 is seen as a hallmark of apoptotic cell death, acting as the final executor of apoptosis. 17 In the present study, western blotting analyses indicated lower levels of both C-caspase3 and Bax, whereas expression of Bcl2 was increased, in the calcitriol group relative to the SCI group. Furthermore, both immunohistochemistry for C-caspase3 and TUNEL staining showed significant decreases in the number of apoptosis-positive cells in the spinal cord lesions of calcitriol-treated rats.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have shown that Bcl2 exerts an antiapoptotic effect, 15 whereas Bax participates in the induction of apoptosis; 16 activation of C-caspase3 is seen as a hallmark of apoptotic cell death, acting as the final executor of apoptosis. 17 In the present study, western blotting analyses indicated lower levels of both C-caspase3 and Bax, whereas expression of Bcl2 was increased, in the calcitriol group relative to the SCI group. Furthermore, both immunohistochemistry for C-caspase3 and TUNEL staining showed significant decreases in the number of apoptosis-positive cells in the spinal cord lesions of calcitriol-treated rats.…”
Section: Discussionsupporting
confidence: 53%
“…Bcl-2 and Bax are two primary genes responsible for the regulation of apoptotic cell death, and their individual products possess opposing functions (24). Bcl-2 is functionally characterized as the apoptosis-suppressing factor, whereas Bax is considered as the apoptosis-promoting factor (25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that mild changes in the external environment that affect circadian rhythm may alter cognition. Chronic sleep fragmentation has been shown to affect autophagy proteins in the hippocampus (123) that may affect memory and cognition (48, 56, 102, 124, 125). Autophagy in the hippocampus also is depressed during the absence of the PER1 circadian clock protein that may worsen the pathology of cerebral ischemia (126).…”
Section: Circadian Clock Genesmentioning
confidence: 99%